Pengaruh Harga dan Pendapatan Terhadap Permintaan Kopi Kekinian Melalui Kualitas Produk pada Generasi Z di Convenience Coffee Store Jakarta Timur - Rosario Velicia Ticoalu; Dicky Iranto; Tuty Sariwulan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of price and income on contemporary coffee demand through product quality among Generation Z at convenience coffee stores in East Jakarta. This research uses a quantitative approach with a survey method through the distribution of questionnaires to respondents who have purchased coffee at convenience coffee stores. The number of respondents in this study was 219 people, selected using a purposive sampling technique. The data analysis method used in this study is Partial Least Square (PLS) with the assistance of SmartPLS software to test the relationships between variables in the research model. The results show that price does not have a significant direct effect on coffee demand, while income and product quality have a positive and significant effect on coffee demand at convenience coffee stores. In addition, the results also indicate that price and income have a positive and significant effect on product quality. In testing the indirect effects, it was found that product quality is able to mediate the effect of price on coffee demand and also mediate the effect of income on coffee demand. This indicates that consumers do not only consider price when purchasing coffee, but also pay attention to the quality of the product offered and their purchasing power which is influenced by their income level. Based on these findings, it can be concluded that income and product quality are important factors influencing contemporary coffee demand at convenience coffee stores, while price does not directly affect demand but plays a role through consumers’ perceptions of product quality. This study is expected to contribute to the development of economic knowledge, particularly in the field of consumer behavior, and to serve as a reference for convenience coffee store businesses in determining pricing strategies and improving product quality.